Tezuka's manga life - Lunning, Frenchy (Mechademia, 2013)
Known as the "Walt Disney of Japan" it is no surprise that Tezuka Osamu is still the best-known manga creator to Western fans. Current scholarship has uncovered the profound complexity and ambiguity not only of his work but of the man, the artist, and his life-dismantling his position as the god of manga. Contributors to this volume of Mechademia-a series devoted to creative and critical work on anime, manga, and the fan arts-analyze Tezuka and his complicated approaches toward life and nonlife on earth, as well as his effect on the lives of other manga artists. Using essays and reprints of Jap